2012
DOI: 10.1016/j.juro.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis Associated with Sleep Disordered Breathing in Children with Sickle Cell Anemia

Abstract: Purpose Enuresis and sleep disordered breathing are common among children with sickle cell anemia. We evaluated whether enuresis is associated with sleep disordered breathing in children with sickle cell anemia. Materials and Methods Baseline data were used from a multicenter prospective cohort study of 221 unselected children with sickle cell anemia. A questionnaire was used to evaluate, by parental report during the previous month, the presence of enuresis and its severity. Overnight polysomnography was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
(24 reference statements)
5
34
1
Order By: Relevance
“…The prevalence rate of NE in children with SCA decreases with increasing age from 29.7% at age 4-8 years to 9% at age 18-20 years ( Figure 1) [6,9,10,12,16,17,19,20]. A similar trend was also observed in enuretic normal children [26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…The prevalence rate of NE in children with SCA decreases with increasing age from 29.7% at age 4-8 years to 9% at age 18-20 years ( Figure 1) [6,9,10,12,16,17,19,20]. A similar trend was also observed in enuretic normal children [26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 60%
“…The effect of gender on the prevalence rate of NE was reported by 12 studies. Boys were reported by 10 studies to have higher prevalence rate than girls [6,[9][10][11][12]15,16,[19][20][21], equal rates in both sexes was reported by one study [13] and one study reported a higher rate in females [17]. These findings are similar to those reported in normal children with NE [28,[30][31][32][33][34][35].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations